Co‐constructing family therapy in the Asian Chinese family diasporas of mainland China, Malaysia, Macau, Singapore and Taiwan. Issue 2 (April 2017) - Sim, Timothy; Yi Fang, Xiao; Chan, Simon; Teik Cheok Loy, Johnben; Sng, Sharon; Lo, Rebecca; Chao, Wentao; Singh, Reenee
Abstract : Asian Chinese families are experiencing constant changes. While commonly known cultural themes such as 'face', 'hierarchy', 'harmony' and 'filial piety' are useful references and important caveats in clinical settings, they are most useful when the context of larger socio‐economic and political developments of recent decades is taken into account. This article is co‐authored by seven experienced Asian therapists from China, Hong Kong, Macau, Malaysia, Singapore, Taiwan and the United Kingdom. They share their insights into working with Chinese families in Asia. In addition to considering cultural dimensions, the authors attempt to consolidate the understanding of Asian Chinese families by focusing on the effects of socio‐economic and political development. Other than focusing on the unique characteristics and challenges of working with Chinese families in their region, they highlight the most useful therapeutic stances and approaches when working with Asian Chinese families. Practitioner points: Be mindful that changing family structures affect family dynamics, childcentric values and work‐life balance. Chinese families expect to receive advice and instruction. Therapists need to be direct and authoritative where appropriate to avoid causing dissatisfaction Chinese families can be helped to negotiate their emerging needs for the differentiation of self A possible therapeutic option is use of self and the ability to embrace uncertainty